Implementasi AI Untuk Meningkatkan Kemampuan Bahasa Inggris Siswa MA Model Zainul Hasan - Eva Sulistiana; Arda Adianto; Wardatun Nadzifah (AMMA : Jurnal Pengabdian Masyarakat, 2025)
English proficiency is recognised as one of the academic strengths promoted at Madrasah Aliyah Model Zainul Hasan; however, the overall competence of students remains relatively low. Several factors contribute to this condition, including limited environmental support, insufficient opportunities for practice, challenges in pronunciation and grammar, and low learner confidence. To address these issues, a community service programme was designed to introduce students to the concept of Artificial Intelligence (AI) and its pedagogical potential in English language learning. The programme consisted of three stages: preparation, implementation, and evaluation. In the preparation stage, the team identified Grade XI students with low English proficiency based on information provided by the homeroom teacher and subsequently arranged a targeted activity schedule. The implementation stage, conducted on 28 May 2025, involved delivering material on “The Use of AI in English Language Learning,” followed by practical sessions using Duolingo and Grammarly. Students explored key features of both applications and completed exercises related to grammar, pronunciation, and sentence construction. The session lasted for two hours. During the evaluation stage, the team documented challenges encountered and collected feedback from school partners to refine future activities. Overall, the programme enhanced students’ understanding of AI-based learning tools and increased their motivation to engage in independent English practice. The accessibility and interactive nature of Duolingo and Grammarly contributed to students’ improved confidence and willingness to utilise AI applications in their learning process .